Políticas sonoras y música popular en el reciente conflicto social peruano (2022-2023) - Mónica Cárdenas Moreno (Caravelle)
This article analyses the government's use of Peruvian musical folklore and its relevance to the protesting population in the context of the current social conflict. Between 2022 and 2023, the government deployed a cultural and sound policy with the aim of legitimising itself, concealing its repression of demonstrators and delegitimising social protest. For its part, the population accompanies its mobilisations with music, makes political use of festivities and dances to express its rejection of the government, and creates a series of songs that seek to structure a network that channels protests into new democratic forms of participation.